Pelatihan Pengolahan Limbah Pertanian Dan Peternakan Menjadi Pupuk Organik Di Desa Kalinilam Kabupaten Ketapang - Ratnawati Hermanto, Sarwendah; Setiawan, Beny; Jatsiyah, Venti; Susanto, Anto; Nurhayati, Nurhayati; Rosmalinda, Rosmalinda; Sopiana, Sopiana; Fitry Ramanda, Rika; Syawaldi, Syawaldi; Kurniawan, Tardi (Literasi Jurnal Pengabdian Masyarakat dan Inovasi, 2025)
Most of the people in Delta Pawan District are farmers and breeders. The number of agricultural business households in Delta Pawan District is 354 cultivating food crops, 640 cultivating horticultural crops and 786 breeders. This shows that the availability of raw materials for making organic fertilizers is very abundant. The problem that has occurred until now is that the waste from agricultural and livestock products has not been utilized optimally by the community due to limited tools and knowledge in processing it into organic fertilizer. The purpose of this activity is to provide motivation and knowledge to the residents of Kalinilam village to utilize agricultural and livestock waste into organic fertilizer which is abundantly available. The method used to overcome these problems is to provide training to Kalinilam villagers on how to process agricultural and livestock waste into organic fertilizer using a compost chopper. This service activity will be carried out in July 2024 with 2 stages, namely socialization and counseling as well as training and assistance in making compost. The result of the service of this training program is an increase in the knowledge of villagers about processing agricultural and livestock waste into organic fertilizer so that it can increase the utilization of waste into more useful products